Ephesians and Colossians in the Greek New Testament for the English reader. - Wuest, Kenneth S. (Grand Rapids, MI Eerdmans, 1953)
Includes bibliographical references and index.
Donated by Mrs F. Hunter. Autographed by author.
Keywords: Bible. N.T. Ephesians -- harmonies; Bible. N.T. Colossians -- harmonies